АІ tools for teaching foreign languages in higher education institutions. - Супрун, Олена Миколаївна; Suprun, Olena (My University, 2023)
The global impact of artificial intelligence (AI) involves a change in approaches, from restructuring the social system to learning and management processes in education. Therefore, there is no choice but to accept artificial intelligence as a necessity and an effective way of improving the educational processes at both classroom and system levels.
Інструменти ШІ для навчання іноземних мов у вищому заклади освіти.